2007
DOI: 10.1111/j.1600-0722.2007.00437.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of soluble CD14 in saliva of young patients with dental caries

Abstract: It is generally accepted that salivary components are important for dental health, but to date no clear correlation has been found between one or more of these components and the outcome of dental caries. The identification of salivary factors preventing, favoring or signaling dental caries might help to control the disease. In the present study, western blotting analysis of whole saliva from 20 healthy caries-free children showed the presence of the soluble form of CD14, a bacterial pattern-recognition recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…The malnourished children developed increased caries and chronic malnutrition in growing children enhances the cariogenic potential stemming from fermentable carbohydrates (Johansson et al, 1992). Studies also demonstrated that the absence (Lenander-Lumikari & Loimaranta, 2000;Uehara et al, 2003;Bergandi et al, 2007) due to deletion of locus (Klingberg, 2007) related to salivary soluble CD14 could represent a useful index of caries activity. Enamel hypoplasia, salivary glandular hypofunction and saliva compositional changes might be mechanisms through which malnutrition is associated with caries (Psoter et al, 2005).…”
Section: Resultsmentioning
confidence: 92%
“…The malnourished children developed increased caries and chronic malnutrition in growing children enhances the cariogenic potential stemming from fermentable carbohydrates (Johansson et al, 1992). Studies also demonstrated that the absence (Lenander-Lumikari & Loimaranta, 2000;Uehara et al, 2003;Bergandi et al, 2007) due to deletion of locus (Klingberg, 2007) related to salivary soluble CD14 could represent a useful index of caries activity. Enamel hypoplasia, salivary glandular hypofunction and saliva compositional changes might be mechanisms through which malnutrition is associated with caries (Psoter et al, 2005).…”
Section: Resultsmentioning
confidence: 92%
“…For caries, previous works in saliva have mainly focused on human-host attributes such as Glucosyltransferase B [23], antimicrobial peptides [24], past caries experience [25], soluble CD14 [26] and trace elements [27], while only a few have exploited individual microbial features, such as specific microbiological counts [28] and microbial nitrate reductase activities [29]. Few global functional analysis and comparison of saliva microbiota function was available, due to (i) the organismal complexity of the microbiota [9] and (ii) the observations that metagenome-sequencing based functional comparison of microbiota can be hampered by sequencing biases [30], the paucity of reference genomes and the small percentage of annotatable reads [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…The genetics of dental caries is thought to be very complex, with many biological mechanisms affecting cariogenesis and operating over long periods of time. Such mechanisms may include genes related to dietary choices (such as taste [Wendell et al, 2010] and olfactory receptors), immune response to pathogens [Bergandi et al, 2007], tooth enamel composition [Slayton et al, 2005], tooth morphology, saliva composition and flow rate, oral health behaviors, transmission of cariogenic bacteria among hosts [Law et al, 2007], and others. Genes acting through these and other avenues, some likely interacting with environmental factors, may each contribute only slightly to overall caries risk, and therefore teasing out the complex interplay of genetic and environmental risk factors represents a necessary challenge for better understanding of the multifactorial nature of dental caries.…”
Section: Discussionmentioning
confidence: 99%